timberline mapped for West Siberia Plain and Alaska ... - Zhang, Tianqi (Zenodo, 2023)
This dataset contains timberlines, which are the frontiers of continuous forests (i.e., taiga), mapped for the entire West Siberia Plain and part of Alaska, with spatial extents also provided. The source data used for timberline delineation were collected from the "tree-coverfraction" variable in the Copernicus Global Land Service product from the year 2019. Timberlines mapped from Landsat global forest cover change (GFCC) (variable: "tree_canopy_cover," year: 2015) and MODIS vegetation continuous field (VCF) (variable: "Percent_Tree_Cover," year: 2020) are also available but only for a small area. The timberline delineation approach takes inspiration from the seeded region-growing segmentation, which effectively captures the frontiers of continuous forests in Landsat imagery while substantially reducing the spatial variability in canopy surfaces present in the timberlines mapped by thresholding tree fractional cover (e.g., 30%). For more details regarding the methodology, please refer to our paper (in ...